Surface roughness and wear performance of Bioflx versus stainless-steel primary crowns (an in-vitro study) - Nancy Mohamed Metwally; Enas A. Elshenawy; Lamis Ahmed Elghareb (BMC Oral Health, 2025)
Abstract Background Different kinds of crowns are used to restore primary teeth. Prefabricated crowns made of zirconia and stainless steel are frequently used. Bioflx crowns are a flexible and attractive substitute that combines the qualities of zirconia and stainless steel. Aim This study aimed to compare BioFLX crowns to stainless-steel crowns regarding surface roughness and wear behavior. Methods Two experimental groups based on the crown material (N = 14/group); group (1): stainless-steel crowns (SSC) and group (2): BioFLX crowns (FLX-C) were compared for surface roughness and wear resistance. Surface roughness was measured using an optical profilometer (white light interferometry, 20X objective lens). For wear measurement, seven primary molars for each group were prepared to receive crowns. Specimens were dynamically loaded (vertical loading, 50 N, 1.2 Hz) up to 100,000 cycles in a chewing simulator, and then wear volume was measured digitally using color mapping method. Data was analyzed using an independent T-test at a significant level of P < 0.05. Results The FLX-C group had lower mean surface roughness (Ra)than the SSC group, however, the difference was not statistically significant according to the independent T-test (T = 0.704, P = 0.495). The FLX-C group experienced decreased wear volumes compared to the SSC group, with a significant difference between the two groups (T = 4.524, P = 0.001). Conclusions Within the limitations of this study, it can be concluded that, in addition to their aesthetic superiority over SSC, BioFLX crowns have considerable wear resistance under several chewing cycles. Furthermore, their average surface roughness is comparable to that of SSC.